Porifera from the Argentine Sea: Diversity in Patagonian scallop beds - Schejter, L.; Calcinai, B.; Cerrano, C.; Bertolino, M.; Pansini, M.; Giberto, D.; Bremec, C. (Italian Journal of Zoology, 2006)
Porifera are a frequently collected taxon in the invertebrate by-catch of the Patagonian scallop Zygochlamys patagonica (King & Broderip 1832) fishery. In order to prevent the destruction of the exploited environments in the Argentine Sea, it is important to know in detail the taxonomic composition of the benthic assemblages. We present here the first study on the sponge assemblage associated with the mollusc species exploited. Thirteen species of Demospongiae (four of which are new records for the Argentine Sea) have been identified, confirming the importance of this phylum as a major component of the scallop bed community.